RESPONSE OF DIFFERENT NODAL AND INTERNODAL EXPLANTS ON IN VITRO SHOOT REGENERATION OF AQUATIC PLANT-SHINNERSIA RIVULARIS WEISS-GRÜN - M. Kratataş; E. Kaya; M. Aasim (Journal of Animal and Plant Sciences, 2018)
Aquatic plants are the primary and secondary producers of the ecosystem and also important part of aquatic industry. Shinnersia rivularis is an important ornamental plant of aquarium industry due to presnece of white veins on the leaves. S. rivularis is mainly vegetatively propagated. This study is the first report of propagating S. rivularis under in vitro conditions. Five different explants divided into two groups of nodal segments (shoot tip, 1st and 2nd nodal segment) and internodes (1st and 2nd internode) were cultured on agar solidified MS medium without any plant growth regulators (PGR) or enriched with 0.05-0.80 mg/l BA+0.20 mg/l NAA for eight weeks. 50-75 % shoot regeneration frequency was recorded irrespective of explant type or plant growth regulators (PGR). Shoots per explants ranged for shoot tip (4.33-12.71), 1st nodal segment (6.24-15.61), 2nd nodal segment (4.99-12.50), 1st internode (4.67-11.37) and 2nd internode (5.03- 11.93). In general, maximum and minimum number of shoots per explants with average shoot length above 1 cm were recorded on MS medium containing 0.20 mg/l BA+0.20 mg/l NAA irrespective of explant type. In vitro regenerated shoots were rooted on agar solidified MS medium enriched with 1.0 mg/l IBA followed by successful   adaptation in the aquarium provided with tap water (pH ≈8.5) and oxygen. 80 % of plants transferred to aquarium survived and continued their growth. This work can be employed for commercial propagation of S. rivularis and for further biotechnological studies
Keywords: Aquatic plant; Explant; In vitro; Internodes; Nodal segments